ANALISIS PENGUASAAN KATA SAMBUNG "SUOYI" DAN "YUSHI" PADA MAHASISWA ANGKATAN 2016 PRODI BAHASA MANDARIN UNTAN - Meise Marcella; Ina Ina; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractGrammar in chinese language is the most important thing for students in learning this language, because various words and sentences are combined into sentence patterns. Among the 13 kinds of grammar pattern words, conjunctions are one of the important words. The conjunction is used to connect two words, phrases and clauses. In various types of conjunctions, "Suoyi" and "Yushi" are conjunctions that we often use. "Suoyi" is a word that used to express a result or end in a sentence. While "Yushi" is used to state the conditions in the final sentence after the conditions stated in the initial sentence. Occurs when these two words can replace each other when used, because "Suoyi" and "Yushi" have differences and also similarities in their usage patterns, so that sometimes these two words cannot replace each other. To find out The Level of Mastery and Level of Difficulty in Students of The 2016 Chinese Language Study Program FKIP Tanjungpura University on the use of the conjunctions "Suoyi" and "Yushi", the researcher conducted research by giving tests to students. The results showed that the ability of students to use the words "Suoyi" and "Yushi" were the same. Students often make mistakes because they do not understand the grammar of the use of these two words, therefore there are several test questions that have a fairly high error rate. Keywords: Conjunction, “Suoyi” and “Yushi”, Analysis of astery